Association between stent length and number and the risk of in-stent restenosis in patients after percutaneous coronary intervention: a systematic review and meta-analysis - Cai, Chanchun; Lu, Lingfen; Ji, Xiaojun; Shi, Zhongping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe association of stent length and number with the risk of in-stent restenosis (ISR) following percutaneous coronary intervention (PCI) in patients with coronary artery disease (CAD) has been widely reported, yet findings remain inconsistent across studies. To clarify this relationship, we conducted a meta-analysis of observational studies evaluating the impact of stent length and number on ISR risk after PCI in CAD patients.MethodsCase-control studies addressing stent length, stent number, and ISR after PCI in CAD patients were systematically searched in electronic databases including VIP, Wanfang, CNKI, Chinese Biomedical Literature Database, PubMed, Web of Science and the Cochrane Library from inception until June 2025. The Risk Of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool was used to assess study quality. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random-effects model. All analyses were performed with Review Manager version 5.4.ResultsEighteen studies involving 6,585 participants were included. Meta-analyses indicated that both stent length [OR = 1.05, 95% CI (1.04, 1.07), P < 0.00001] and stent number [OR = 3.01, 95% CI (1.97, 4.59), P < 0.00001] were significant risk factors for ISR after PCI in CAD patients.ConclusionThis meta-analysis supports the conclusion that stent length and number are associated with an increased risk of ISR after PCI in CAD patients. However, given the limited number and moderate quality of the included studies, these findings should be interpreted with caution and validated by further high-quality research.